(untitled) - Anthony C Winkler (Fort Worth, 2000)
This book offers two full legth models of the research paper - one in MLA ( Modern Language Association ) and the other in the APA ( American Psychological Association ) style. Each paper is fully annotated in the margins to point out various research techniques and conventions that the writer has used. Indeed, both models are so comprehensive that the student could easily in either the MLA or APA style merely by imitating the appropriate paper.
Keywords: essays - study and teaching,rhetoric